Seeking Unity Where It Is and Is Not - Piekkola, Brad (International Review of Theoretical Psychologies, 2026)
Since its inception as a science, psychology has been characterized by disunity and opposition. Over time it increasingly differentiated into various specializations. Such fragmentation led to doubts whether psychology could be a coherent discipline. After considering some of the solutions for resolving disunity, the source of the problem is sought in the historical development of the discipline. The emulation of the established sciences and their methods meant the adoption of strategies of reductionism and elementalism and a quest for abstract, universal principles that transcended individuality. Whole human beings were subjected to analysis and dismemberment and the resulting abstractions were hypostasized and disengaged from their context—the organized whole. The result was an apparent irreconcilability between specializations. Rather than trying to amalgamate the divergent disciplines, it is argued that humans, prior to analytic dismemberment, are a basis for unification. It is within the undivided person that the phenomena of the different disciplines cohere. Consequently, experimental findings must be recontextualized and concretized by returning to whole persons for validation. It is through concrete validation that specializations are reunited, and division overcome. Finally, it is contented that a science of the unified, psychological-being-in-context is needed